Aktif, Cerdas, Sehat: Literasi Jasmani sebagai Fondasi Pendidikan Karakter di SMPN 5 Tanjung Jabung Timur: (Active, Intelligent, Healthy: Physical Literacy as the Foundation of Character Education at SMPN 5 Tanjung Jabung Timur) - Saputra, Endarman; Hadinata, Reza; Oktadinata, Alek; Daya, Wawan Junresti; Iqroni, David; Yuliawan, Ely (Jurnal JUPEMA, 2025)
This community engagement initiative aims to enhance understanding and awareness of physical literacy among teachers and students at SMPN 5 Tanjung Jabung Timur. The programme seeks to establish physical literacy as a fundamental element for fostering the development of students who are active, intellectually engaged, and healthy. Using an interactive approach that combines outreach and training, the activities introduce a comprehensive concept of physical literacy, encompassing the necessary knowledge, practical skills, and positive attitudes towards sustained physical activity. This activity method involves structured counselling sessions, facilitates group discussions, and practical implementation of easily replicable physical activities suitable for the school environment. The results clearly demonstrate a significant increase in participants' knowledge of the importance of consistent physical activity, alongside a high awareness of the intrinsic relationship between physical fitness, cognitive development, and the cultivation of positive character traits. Consequently, the programme is positioned as a potential model for enhancing character education based on physical activity within educational institutions. Abstrak. Inisiatif pelibatan masyarakat ini berupaya meningkatkan pemahaman dan kesadaran literasi jasmani di kalangan guru dan siswa di SMPN 5 Tanjung Jabung Timur. Program ini bertujuan untuk menetapkan literasi jasmani sebagai elemen dasar untuk menumbuhkan pengembangan karakter siswa yang aktif, terlibat secara intelektual, dan sehat. Menggunakan pendekatan interaktif yang menggabungkan penjangkauan dan pelatihan, kegiatan ini memperkenalkan konsep literasi jasmani yang komprehensif, yang mencakup pengetahuan yang diperlukan, keterampilan praktis, dan sikap positif terhadap aktivitas fisik yang berkelanjutan. Metode kegiatan ini melibatkan sesi konseling terstruktur, memfasilitasi diskusi kelompok, dan implementasi praktis aktivitas fisik yang mudah ditiru yang sesuai dengan lingkungan sekolah. Hasil dengan tegas menunjukkan peningkatan yang signifikan dalam pengetahuan peserta mengenai pentingnya aktivitas fisik yang konsisten, di samping kesadaran yang tinggi tentang hubungan intrinsik antara kebugaran fisik, perkembangan kognitif, dan kultivasi sifat-sifat karakter positif. Akibatnya, program ini diposisikan sebagai model potensial untuk memperkuat pendidikan karakter berbasis aktivitas fisik di dalam lembaga pendidikan.